Jan Jakub Rousseau o naturze kobiety - Baranowska, Marta (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Rousseau described his passionate feelings for several women in his life in his Confessions. Certainly Le Vasseur had some influence in Rousseau’s concept of the ideal woman. Rousseau primarily claimed that nature has created man happy, good and eaqual, but society depraves him and makes him miserable. Rousseau claimed that women is a human being. Rousseau outlines his theories for the ideal education for women in Chapter V of Emile. For Rousseau, everything man and woman have in common belongs to the species, and everything which distinguishes them belongs to the sex. He viewed women’s options as entirely limited to the roles of wife and mother. Women will always be in subjection to a man and she will never be free to set her own opinion above his. Rousseau described Sophie who had been educated to be Emile’s ideal wife. This brief description of female nature and education sparked an immense contemporary response. For example Mary Wollstonecraft attacked Rousseau and his arguments in A Vindication of the Rights of Woman
Keywords: Rousseau, Jean Jacques (1712-1778); kobiety; feminizm; płeć